2015
DOI: 10.1021/ef501961s
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Approach to the Prediction and Analysis of Temperature Inhomogeneity in Rapid Compression Machines

Abstract: 1Substantial progress has been made in understanding and reducing temperature inhomogeneity in rapid compression machines (RCMs) with the help of computational modelling. To date, however, it has not been possible to investigate and map the full range of possible RCM designs, working gases and operating conditions. In this article, we present a framework which simplifies the task of comprehensive and general RCM performance prediction. A set of thermophysical and geometrical parameters have been defined to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 14 publications
(65 reference statements)
1
26
0
Order By: Relevance
“…From these studies, it is clear that properly configuring the piston crevice for particular machine geometry and operating conditions is key to adequately suppressing the corner vortex formation, and that a single configuration may not be appropriate across a wide range of facilities, or a range of experimental conditions explored during an experimental campaign. Yousefian et al [150] used non-dimensional scaling to highlight that Peclet number, bore:stroke aspect ratio, and crevice volume : swept volume ratio are key overall parameters towards suppressing fluid motion and minimizing thermal non-uniformities.…”
Section: Control Of the Reacting Gasmentioning
confidence: 99%
“…From these studies, it is clear that properly configuring the piston crevice for particular machine geometry and operating conditions is key to adequately suppressing the corner vortex formation, and that a single configuration may not be appropriate across a wide range of facilities, or a range of experimental conditions explored during an experimental campaign. Yousefian et al [150] used non-dimensional scaling to highlight that Peclet number, bore:stroke aspect ratio, and crevice volume : swept volume ratio are key overall parameters towards suppressing fluid motion and minimizing thermal non-uniformities.…”
Section: Control Of the Reacting Gasmentioning
confidence: 99%
“…Three simulations are conducted for different mesh sizes at the initial pressure and temperature of 50 kPa and 298 K for nitrogen, which is described in detail in the mesh methodology section. The results of previous study [9] showed that various initial pressures resulted in different velocity and temperature distributions inside the RCM main chamber. Therefore, another simulation is conducted for the selected mesh at initial pressure and temperature of 100 kPa and 298 K for nitrogen to study the effect of operating conditions.…”
Section: ∆ (5)mentioning
confidence: 96%
“…In this study, seven LES simulations are conducted to study mesh sensitivity, the effects of operating conditions on flow regimes, and the assessment of temperature inhomogeneity correlation which was developed in previous study [9]. Three simulations are conducted for different mesh sizes at the initial pressure and temperature of 50 kPa and 298 K for nitrogen, which is described in detail in the mesh methodology section.…”
Section: ∆ (5)mentioning
confidence: 99%
See 2 more Smart Citations